Nomogram prediction of individual prognosis of patients with hepatocellular carcinoma. Issue 1 (December 2017) - Wan, Gang; Gao, Fangyuan; Chen, Jialiang; Li, Yuxin; Geng, Mingfan; Sun, Le; Liu, Yao; Liu, Huimin; Yang, Xue; Wang, Rui; Feng, Ying; Wang, Xianbo
Abstract Background The purpose of this study was to develop an effective nomogram capable of estimating the individual survival outcomes of patients with hepatocellular carcinoma (HCC), and compare the predictive accuracy and discriminative ability with other staging systems. Methods The nomogram was established based on a retrospective study of 661 patients newly diagnosed with HCC at the Beijing Ditan Hospital (Beijing, China), Capital Medical University, between October 2008 and July 2012. The predictive accuracy and discriminative ability of the previously developed nomogram were assessed by C-index and calibration curves, and were compared to seven current commonly used staging systems. The results were validated, using a bootstrap approach to correct for bias, in a prospective study of 220 patients consecutively enrolled between August 2012 and March 2013. Results Multivariate analysis of the primary cohort for survival analysis identified the independent factors to be aspartate aminotransferase, ɣ-glutamyl transpeptidase, white blood cell count, neutrophil-to-lymphocyte ratio, prothrombin activity, α-fetoprotein, tumor number and size, lymph node metastasis, and portal vein involvement, which were all included to build the nomogram. The calibration curve for predicting the probability of survival showed consistency between the nomogram and the actual observation. The C-index of the nomogram was 0.81 (95% confidence interval, 0.79–0.82), which was statistically better than that of the Tumor, Node, Metastasis staging (0.71), Barcelona Clinic Liver Cancer staging (0.77), Okuda (0.62), Japan Integrated Staging (0.73), Cancer of the Liver Italian Program score (0.76), Chinese University Prognostic Index (0.68), and the Groupe d' Etude et de Traitement du Carcinome Hepatocellulaire Prognostic classification (0.65) (p < 0.001 for all). The results were validated in the prospective validation cohort. Conclusions The prognostic nomogram resulted in more accurate individualized risk estimates for overall survival in HCC patients.